Plasma Aβ40, Aβ42 and Aβ‐clearance proteins as blood biomarkers for Alzheimer's disease, subjective cognitive decline, and MCI. (31st December 2021) - Ito, Hitomi; Shan, Liu; Hata, Naoko; Korenaga, Tatsumi; Suzuki, Hideaki; Meno, Kohji; Takihara, Takanobu; Akatsu, Hiroyasu; Matsukawa, Noriyuki; Asada, Takashi; Arai, Tetsuaki; Uchida, Kazuhiko
Abstract: Background: For early intervention and prevention of dementia, diagnostic biomarkers for MCI and preclinical Alzheimer's disease (AD) are important. amyloid β (Aβ) and tau are known as biomarkers for AD, and the CSF Aβ40 / Aβ42 ratio is clinically useful for diagnosis of AD. We have reported that three proteins in serum related to Aβ clearance: ApoA1, complement protein C3 and transthyretin (TTR) are useful as blood biomarkers for MCI (Triple marker). Plasma Aβ has been shown to correlate with amyloid PET, however, its clinical utility in MCI and AD diagnosis is unclear. Therefore, we investigated usefulness plasma Aβ in addition to the triple marker as blood test for MCI and AD. Here we analyzed plasma levels of Aβ40, Aβ42 and Triple marker in MCI and AD as diagnostic markers. Method: A total of 909 cases consisting of 354 non‐demented control (NDC), and 76 subjective cognitive decline (SCD), 312 MCI, and 167 AD diagnosed according to ADNI neuropsychological criteria were selected in the multicenter clinical study. The positron emission tomography (PET) using with [18F] Florbetapir was performed 24 APOE4‐carring SCD and MCI subjects. Plasma Aβ40, Aβ42 were measured by ELISA (EUROIMMUN, Lübeck) . Plasma levels of ApoA1, TTR, complement C3 was measured as described previously (Liu et al., Alzheimer Dement (Amst) 2019). Result: Plasma ApoA1 and complement C3 levels were decreased in progression of the disease. Plasma Aβ40 / 42 ratio showed ROC AUC = 0.82 and 0.67 in AD vs. NDC and MCI vs. NDC, respectively. Combination of plasma levels of Aβ40 / 42 ratio and Triple marker (ApoA1, TTR, C3) showed AUC = 0.85 (80% sensitivity and 85% specificity) in AD vs. NDC and AUC = 0.76 (76% sensitivity and 70% specificity) in MCI vs. NDC. Aβ40 / 42 ratio and TTR were significantly decreased in amyloid‐positive subjects (SUVR≥1.10) compared to amyloid‐negative subjects (SUVR<1.10). Conclusion: Combination of plasma Aβ40 / Aβ42 ratio and Triple marker is a useful blood test for not only AD but also the early stages of cognitive decline.